Penja fish (Genus: Sicyopterus) from Karama River, West Sulawesi, Indonesia: Growth Pattern and Habitat Characteristics - CUT MUTHIADIN MUTHIADIN; Isna Rasdianah Aziz; HASYIMUDDIN HASYIMUDDIN; FATMAWATI NUR; ST. AISYAH SIJID; SAIFULLAH AZMAN; RENNY KURNIA HADIATY; ILHAM ALIMUDDIN (Society for Indonesian Biodiversity, 2020)
Sicydiinae gobies have been widely collected and identified throughout tropical indo-pacific, except in Karama River, Mamuju, West Sulawesi, Indonesia. Penja was the Gobi fish’s local name, where the pelvic disc is adherent to the belly. This study aims to describe the habitat and growth patterns of genus Sicyopterus in Karama river, which passes through three sub-districts from upstream to downstream. The research was conducted in Karama River from four sites: Kalumpang, Bonehau, Arassi, and Kalonding. Fish growth was described by Deroberts and William model, and continued with habitat characteristics. The total number of fish from four sites about 71 adults Gobiidae fish, identified as family Gobiidae: Sicyopterus longifilis and Sicyopterus pugnans. The average growth pattern in all sites is isometric negative (b<3), except in the Kalumpang sites, growth pattern for Sicyopterus longifilis is isometric (b=3) whereas in Sicyopterus pugnans in the Kalumpang sites growth pattern is positive allometric (b>3).